Female elements in figuratively symbolic ideas of Slavic mythology - Diana Chuvashova (Cхід, 2016)
In article it is proved that in the life of the Slavic peoples the special place held by a woman. "Female" cults and beliefs reflected in figurative and symbolic representations of Slavic mythology. It recorded the stereotypes, archetypes and symbols which are then in an ancient society has formed certain social attitudes and cultural canons. Figuratively symbolic representations in different cultures became the basis of the IN social constructs of identity related cultures. Figuratively, a symbolic representation of Slavic mythology testify to the woman's place in society, her position in the family, relationship with man and environment.